Modulation of Human Immune Response by Echinococcus granulosus Antigen B and Its Possible Role in Evading Host Defenses - Riganò, R. (American Society for Microbiology, 2001)
By directly suppressing the function of certain immune cell subsets and by stimulating other cell populations related to immunopathology, parasite-derived substances play an important role in the chronic establishment of parasitic disease. Our objective was twofold: (i) to investigate further the role of Echinococcus granulosus antigen B (AgB) in the human early inflammatory response by determining its effect on polymorphonuclear cell (PMN) random migration, chemotaxis, and oxidative metabolism and (ii) to determine its action in acquired immunity by evaluating AgB and sheep hydatid fluid (SHF)-driven Th1 (gamma interferon [IFN-γ] and interleukin 12 [IL-12]) and Th2 (IL-4 and IL-13) cytokine production by peripheral blood mononuclear cells (PBMC) from 40 patients who had cured or stable or progressive cystic echinococcosis. AgB significantly inhibited PMN recruitment but left their random migration and oxidative metabolism unchanged. Patients' PBMC stimulated with AgB produced IL-4 and IL-13 but did not produce IL-12. They also produced significantly lower IFN-γ concentrations than did PBMC stimulated with SHF (P = 10(−5)). AgB skewed the Th1/Th2 cytokine ratios towards a preferentially immunopathology-associated Th2 polarization, predominantly in patients with progressive disease. AgB-stimulated patients' PBMC also proliferated less than SHF-stimulated PBMC (P = 9 × 10(−3)). In vitro Th2 cytokine production was reflected in vivo by elevated specific immunoglobulin E (IgE) and IgG4 antibodies binding to AgB. These findings confirm that AgB plays a role in the escape from early immunity by inhibiting PMN chemotaxis. They also add new information on the host-parasite relationship, suggesting that AgB exploits the activation of T helper cells by eliciting a nonprotective Th2 cell response.